Developing Effective Smoking Cessation Treatment Interventions for Individuals with Severe Mental Illness Who are Homeless or Vulnerably Housed - Pettey, Donna Louise (Université d'Ottawa / University of Ottawa, 2015)
While tobacco use remains a leading preventable risk factor for mortality and morbidity in Canada (Patra, Rehm, Baliunas & Popova, 2007), the overall smoking prevalence rate of Canadians has decreased substantially from close to 50% of the population in 1965 to 16.1% of the population in 2012 (Canadian Tobacco Use Monitoring Survey (CTUMS) 2012; Reid, Hammond, Rynard & Burkhalter, 2014). However, up to 85% of individuals with a mental illness continue to use tobacco products (Harris, Parle & Gagne, 2007), contributing to an inequitable distribution of negative health outcomes for this population. Individuals with severe mental illness die an estimated twenty-five years earlier than the general population, with sixty per cent of these deaths due to cardiovascular, pulmonary and infectious disease (Parks, Svendsen, Singer, & Foti, 2006). A recent study that examined specific tobacco-attributable deaths in these populations found that tobacco accounted for 53% of deaths in individuals with schizophrenia, 50% of all deaths for those diagnosed with a depressive disorder, and 48% of all deaths for those with a diagnosis of bipolar disorder (Callaghan et al., 2014). This research project is intended to increase our understanding of what constitutes an effective intervention for smoking cessation and smoking reduction in a population of individuals with severe mental illness who are homeless or vulnerably housed, living in a large urban setting. Two areas of inquiry were proposed. The first inquiry examined data collected as part of a needs assessment to determine the overall prevalence rate of smoking and related behaviours for a population of individuals with severe mental illness receiving services from a community mental health agency. We found that the tobacco use prevalence was 72%, and 62% of smokers had high or very high levels of nicotine dependence; however almost half of respondents (47%) were interested in quitting or reducing tobacco within the next 6 months. Smokers were found to be over 9 times more likely to have a co-occurring substance use disorder (OR=9.44, 95%CI[6.33,14.08]). The second inquiry was a pilot study conducting a randomized controlled trial design to evaluate smoking cessation and smoking reduction outcomes for two groups of individuals (n=61) with severe mental illness receiving different smoking cessation interventions. Clients randomly assigned to the routine Smoking Cessation group (SC-R) received up to 24 weeks of no-cost Nicotine Replacement Therapy (NRT) and clients assigned to the Smoking Cessation Plus group (SC+) received up to 24 weeks of no-cost Nicotine Replacement Therapy (NRT) plus two initial individual sessions of motivational interviewing followed by weekly psychosocial group interventions for up to 24 weeks. Primary outcomes were levels of tobacco use at the 3-month and 6-month follow-up. The 7-day point prevalence abstinence rate measured at 3 months was 21.9% (n=7) for the SC+ group and 13.8% (n=4) for the SC-R group (OR=1.75,95%CI[.46,6.74]). At 6 months, the 7-day point prevalence abstinence rate was 12.5% (n=4) for the SC+ group and 6.9% (n=2) for the SC-R group (OR=1.93, 95%CI[.33,11.41]). Secondary outcomes included change in reported quality of life, physical health and mental health status functioning over the course of the study. We found that there were no statistically significant differences in the smoking quit or smoking reduction rates between the two treatment groups. At the 3-month time point the overall quit rate for both groups combined was 18% (n=11) and at the 6-month time point the quit rate was 10% (n=6). Reduction in the number of daily cigarettes smoked was statistically significant over time (F [1.68, 98.90] = 55.13, p < .001, η p 2 = 0.48) for both groups, as was the overall reduction of the FTND score (F [2, 94] = 17.98, p < .001, η p 2 = 0.28). This research demonstrates that collecting vital tobacco prevalence and dependency information is a straightforward and important task for community mental health agencies. Individuals with mental illness have both the interest and ability to quit or reduce their use of tobacco. Practitioners need to be aware of alternative smoking practices that may contribute to understanding tobacco use patterns and dependence in this population. Other factors such as co-morbid substance use disorder and level of community functioning may influence smoking status and, consequently, how treatment is provided. The findings of the pilot trial demonstrate the feasibility of conducting smoking cessation research with the population. Findings also suggest that a larger definitive trial is warranted to examine the effectiveness of the SC+ intervention. This research adds to the limited but growing knowledge base of how to address tobacco use and provide treatment to this vulnerable group, and will contribute to advances in population health by informing effective interventions with the attendant implications for program and policy development.
Keywords: Smoking cessation; Severe mental illness; Tobacco; Vulnerable populations; Health inequity; Homelessness and housing vulnerability